Antibacterial effect of clove (Eugenia aromaticum) oil extracted from clove cigarettes towards Streptococcus mutans - Jumali, Ahmad Alif Wazir; Satari, Mieke Hemiawati; Dewi, Warta (Universitas Padjadjaran, 2013)
Streptococcus mutans is a commensal bacteria of the oral cavity, particularly found in dental plaque attached to the tooth surface, and can also found in the saliva, buccal mucosa, tongue, and the gingival sulcus. Clove cigarette contains the clove oil used worldwide as a herbal remedy for a variety of health disorders due to its antibacterial, antifungal, and antiviral properties. The purpose of this study was to determined the antibacterial effect of the clove oil contained in the clove cigarette towards Streptococcus mutans as a cariogenic bacteria. The research was an experimental laboratory, which tested the sensitivity of the Streptococcus mutans bacteria taken from the saliva of 10 clove cigarette smokers towards the clove oil extract of the clove cigarette in-vitro by using the Kirby-Bauer method. The study showed that the clove oil extract of the clove cigarette which contained eugenol has antibacterial towards the growth of Streptococcus mutans, and there was a difference of the antibacterial activity between clove oil extracted from minced and combusted clove cigarette. The conclusion of this study was the clove oil extracted from minced clove cigarette had a better antibacterial effect than the combusted clove cigarette.